Volume delivered during recruitment maneuver predicts lung stress in acute respiratory distress syndrome - Beitler, Jeremy R. (Crit Care Med, 2016)
OBJECTIVE: Global lung stress varies considerably with low tidal volume ventilation for acute respiratory distress syndrome (ARDS). High stress despite low tidal volumes may worsen lung injury and increase risk of death. No widely available parameter exists to assess global lung stress. We aimed to determine whether the volume delivered during a recruitment maneuver (V(RM)) is inversely associated with lung stress and mortality in ARDS. DESIGN: Substudy of an ARDS clinical trial on esophageal pressure-guided PEEP titration. SETTING: U.S. academic medical center. PATIENTS: 42 patients with ARDS in whom airflow, airway pressure, and esophageal pressure were recorded during the recruitment maneuver (RM). INTERVENTIONS: A single RM was performed before initiating protocol-directed ventilator management. RMs consisted of a 30-second breath hold at 40 cmH(2)O airway pressure under heavy sedation or paralysis. V(RM) was calculated by integrating the flow-time waveform during the maneuver. End-inspiratory stress was defined as the transpulmonary (airway minus esophageal) pressure during end-inspiratory pause of a tidal breath, and tidal stress as the transpulmonary pressure difference between end-inspiratory and end-expiratory pauses. MEASUREMENTS AND MAIN RESULTS: V(RM) ranged between 7.4 and 34.7 mL/kg predicted body weight (PBW). Lower V(RM) predicted high end-inspiratory and tidal lung stress (end-inspiratory: ß = −0.449, 95% CI −0.664 to −0.234; p < .001; tidal: ß = −0.267, 95% CI −0.423 to −0.111; p = .001). After adjusting for PaO(2)/FIO(2) and either driving pressure, tidal volume, or plateau pressure and PEEP, V(RM) remained independently associated with both end-inspiratory and tidal stress. In unadjusted analysis, low V(RM) predicted increased risk of death (OR 0.85, 95% CI 0.72–1.00; p = .026). V(RM) remained significantly associated with mortality after adjusting for study arm (OR 0.84, 95% CI 0.71–1.00; p = .022). CONCLUSIONS: Low V(RM) independently predicts high lung stress and may predict risk of death in patients with ARDS.